YASMiN : The Recycler - Faruqi, Saadia; Aly, Hatem; Mohn, Kristen (North Mankato, Minnesota, United States: PICTURE WINDOW BOOKS, an imprint of Capstone, 2021)
Yasmin is thrilled about her school's new recycling program. But getting her friends to pitch in is no easy task! Will some creative thinking get Yasmin's friends to be good recyclers?
Audience : Ages 5-7. Audience : Grades K-1.
Keywords: Recycling (Waste) -- Fiction; Schools -- Fiction; Muslims -- United States -- Fiction